The Issue of Methodological Support of Forensic Examination of Locks and Security Seals - S. A. Kruglyak (Теория и практика судебной экспертизы)
The author summarizes the possibilities, achievements, and outlook for developing the methodological framework of toolmark analysis, including the examination of locks and security seals. The significance of toolmark analysis performed on these objects is demonstrated in the context of investigating different types of crimes. The author offers suggestions on the need to develop state-of-the-art forensic methodologies, and to improve the design of locking devices.